THE IMPACT OF YOGA ON THE RELAXATION PROCESS AS AN EFFORT TO MINIMIZE THE ANXIETY LEVEL OF PREGNANT WOMEN IN BIDAN MANDIRI CLINIC, MEDAN, INDONESIA. (May 2018) - Perangin-Angin, Sri Yunita; Sihombing, Faija
No abstract available